Dietary fibre and health in children and adolescents - Edwards, Christine; Xie, C.; Garcia, A. (Cambridge University Press, 2015)
The role of dietary fibre in promoting sustained health has been studied for several decades and in adults there is good evidence that diets rich in high-fibre foods reduce the risk of chronic diseases, including CVD and cancer. Research in this area, however, has been hampered by uncertainties about the definition of dietary fibre which has resulted in many studies measuring fibre in different ways. There is also a wide range of properties and actions of different fibres in the human body, depending on their solubility, viscosity and fermentability by the colonic microbiota. This review considers the epidemiological evidence for dietary fibre and health in children and the current dietary recommendations and measured intakes in several countries using national surveys. In children and adolescents, there is a particular lack of relevant research on which to formulate appropriate dietary fibre recommendations and these are often based on extrapolation from adult data. However, children are not little adults and have differing physiology and nutritional needs as they grow. The dietary recommendations in different countries are based on varying premises and daily amounts. Intakes vary from country to country and on the whole do not meet recommendations. Much more research is needed in children to fully understand the impact of dietary fibre on growth and health in the young to allow more appropriate recommendations to be made.